2020
DOI: 10.1186/s41256-020-00139-2
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for health systems performance assessment: how comprehensive is Ghana’s holistic assessment tool?

Abstract: Background: Measuring the performance of a health system is an essential requirement in creating systems that generate efficient, equitable, patient-focused, accessible and sustainable results. A fundamental requirement for a performance measurement system is the development of an assessment framework within which specific performance measures could be defined and applied regularly. This paper examines the comprehensiveness of Ghana's health system assessment framework called the Holistic Assessment Tool in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…3 This approach has been used to assess health systems, though this has largely been in high-income countries, [4][5][6][7] with fewer such initiatives in the developing world. [8][9][10][11] Additionally, the uptake and use of results from these assessments by decision makers and their impact on system development has been limited. 12 13 The building blocks conceptualisation however only tells part of the story of what a health system entails.…”
Section: Key Questionsmentioning
confidence: 99%
“…3 This approach has been used to assess health systems, though this has largely been in high-income countries, [4][5][6][7] with fewer such initiatives in the developing world. [8][9][10][11] Additionally, the uptake and use of results from these assessments by decision makers and their impact on system development has been limited. 12 13 The building blocks conceptualisation however only tells part of the story of what a health system entails.…”
Section: Key Questionsmentioning
confidence: 99%
“…Many high-income countries have since institutionalized HSPA as an integral component of their respective health systems [ 6 , 12 , 13 ]. However, few studies on HSPA have been documented in LMICs [ 14 17 ]. Examples of these few studies in LMICs include an analysis of district-level HSPA within the context of decentralization in Indonesia [ 18 ]; an assessment of the effect of health system reforms between 2001 and 2006 in Mexico, using a report card approach [ 19 ]; an evaluation of the performance of the healthcare delivery system in 16 states of India, using an econometric approach [ 20 ]; and monitoring of the rapid expansion of health services in Afghanistan, using a balanced scorecard approach [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of the aforementioned assessment programmes, Ghana does not have a full-fledged HSPA tool that provides a holistic health sector-wide approach to assessing health system performance. For instance, our recent analysis revealed that the HAT is merely an assessment tool for monitoring and evaluating the MOH’s annual plans or POWs, as well as assessing progress towards the achievement of the country’s HSMTDPs [ 17 ]. According to WHO, a comprehensive HSPA is balanced in scope, and covers the whole health system and is not limited to specific programmes, objectives or levels of care.…”
Section: Introductionmentioning
confidence: 99%
“…Many high-income countries (HICs) have institutionalized HSPA as an integral component of their respective health systems [6,10,11]. However, few studies on HSPA have been documented in LMICs [12][13][14][15]. Examples of these few studies in LMICs include an analysis of district level HSPA within the context of decentralization in Indonesia [16]; an assessment of the effect of health system reforms between 2001 and 2006 in Mexico, using a report card approach [17]; an evaluation of the performance of the healthcare delivery system in 16 states of India, using an econometric approach [18]; and monitoring of the rapid expansion of health services in Afghanistan, using a balanced scorecard approach [19].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the existence of the aforementioned assessment programs, Ghana does not have a full-edged HSPA tool that provides a holistic health sector-wide approach to assessing health system performance. For instance, our recent analysis revealed that the Holistic Assessment Tool, which is considered more comprehensive relative to the other assessment methods, does not measure key health system dimensions such as responsiveness of the health system and information systems for health [15]. Per the literature, a comprehensive HSPA encompasses measuring and analyzing how well a health system is meeting its overall goals (i.e.…”
Section: Introductionmentioning
confidence: 99%